2019
DOI: 10.1111/jfbc.13129
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency comparison of PGBR extract and γ‐oryzanol in antioxidative stress and anti‐inflammatory properties against metabolic syndrome

Abstract: This research aims to delineate the anti‐inflammatory effect of pregerminated brown rice extract (PE) and γ‐oryzanol on improving metabolic features of high‐fat diet (HFD)‐induced metabolic syndrome (MetS) mouse model. C57BL/6 mice were randomly divided into eight groups: regular diet (RD), HFD, HFD‐combined treatment of 0.5, 5, or 10 mg kg−1 day−1 oral gavage γ‐oryzanol, and 30, 300, or 600 mg kg−1 day−1 PE for 18 weeks. HFD‐fed mice showed overweight, hyperglycemia, hyperlipidemia signs of metabolic disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…It is well known that high-fat diets can induce obesity which represents the risk factors for the development of insulin resistance (IR) and type 2 diabetes (T2DM) [148,149]. Obesity-related diseases such as T2DM induce diabetic wounds and are also associated with rapid cartilage loss and osteoarthritis [150][151][152].…”
Section: Role Of Mscs In Adipocyte Vicinitymentioning
confidence: 99%
“…It is well known that high-fat diets can induce obesity which represents the risk factors for the development of insulin resistance (IR) and type 2 diabetes (T2DM) [148,149]. Obesity-related diseases such as T2DM induce diabetic wounds and are also associated with rapid cartilage loss and osteoarthritis [150][151][152].…”
Section: Role Of Mscs In Adipocyte Vicinitymentioning
confidence: 99%
“…HepG2 cells, obtained from the National Development Center of Biotechnology (Taipei, Taiwan), were maintained as a monolayer culture in complete medium at 37 °C in a humidified 5% CO 2 incubator with medium changed every 2 days. Initially, HepG2 cells were seeded in 6-well plates at a density of 1 × 10 5 cells/well, and treated 100 ng/mL TNF-α for 5 h. Afterward, changing medium containing 10 μM insulin only, 10 μM insulin and 45 ng/mL TNF-α, or 10 μM insulin, 45 ng/mL TNF-α and TDE or KDE (20,25,50, or 100 μg/ mL) stimulated the cells for 16 h. We referred to and modified the method of Kim et al 15 and Lin et al 4 in the cell experiment.…”
Section: Cell Culturementioning
confidence: 99%
“…The relative expression of those proteins in each tissue was quantified by densitometric scanning of the western blots using Image-pro plus software (Media Cybernetics, MD) as previously described. 4…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“… 124 It was suggested that the mechanisms were mediated by γ-oryzanol through its inhibition of inflammatory markers, such as prostaglandin E2 (PGE2), which is involved in the progression of kidney dysfunction. 124 , 125 …”
Section: Biological and Functional Activities Of Rbmentioning
confidence: 99%